Numerical nonlinear analysis of RC beans with un-strengthened and CFRP-strengthened opening drilled under service loads within shear zones (Fracture and Structural Integrity, 2022)
Current research paper deals with reinforced concrete (R.C.) beams numerical modeling and suggested strengthening procedure if it is required to create an opening within their shear zones. Strengthening is assumed to be achieved during different service load application conditions. Reinforced Concrete beams with rectangular or circular opening in shear zone; as critical regions; sustain two concentrated system of loads are tested till failure before and after performing suggested opening assessing technique by means of Carbon Fibers Reinforced Polymer sheets (CFRP). The main aim of this research is simulating real practice situation where the beam is subjected to service loads, supported temporary by means of hydraulic jacks, opening is created and strengthening is performed then jacking supports are released. Results of achieved numerical nonlinear modeling are introduced and influence of strengthening achieving on improving assessed beams almost structural behavior such as initial cracking loads, load deflection curves, cracking patterns, failure loads & modes for reference (without opening), main un-strengthened control beams, and CFRP strengthened opening beams are introduced and analyzed in details. Some important conclusions & recommendations for designer and executive engineers are stated.
Keywords: Service load; Reinforced; Concrete; Beams; Openings; Strengthening; Shear; CFRP; Finite element; ANSYS; Nonlinear analysis